Thermo-elasto-hydrodynamic analysis of bump-type air foil thrust bearings considering misalignment - Markus Eickhoff; Johannis Triebwasser; Bernhard Schweizer (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2023)
In this study, a multi-pad bump-type foil thrust bearing with a taper-land height profile is investigated. A detailed thermo-elastohydrodynamic (TEHD) finite element (FE) model is used comprising all bearing pads instead of only a single pad. Although the single-pad reduction approach is commonly applied, it can not accurately account for the different temperatures, loads, and power losses for individual pads in the case of misalignment. The model accounts for the deformations of the foils on each pad via a Reissner-Mindlin-type shell model. Deformations of the rotor are calculated via the Navier-Lamé equations with thermoelastic stresses and centrifugal effects. The temperature of the top foil and the rotor are calculated with the use of heat diffusion equations. The temperature of each lubricating air film is obtained through a 3D energy equation. Film pressures are calculated with the 2D compressible Reynolds equation. Moreover, the surrounding of the bearing and runner disk is part of the thermodynamic model. Results indicate that the thermal bending of the runner disk as well as top foil sagging are key factors in performance reduction. Due to the bump-type understructure, the top foil sagging effect is observed in simulation results. The study at hand showcases the influence of misalignment between the rotor and the bearing on the bearing performance.